2019
DOI: 10.1093/aob/mcz167
|View full text |Cite
|
Sign up to set email alerts
|

Inherited dimorphism in cleistogamous flower production in Portulaca oleracea: a comparison of 16 populations growing under different environmental conditions

Abstract: Background and Aims Cleistogamy is considered to be an adaptive strategy resulting in plasticity in CH and CL flower production depending on environmental conditions and plant size. The aim of this study was to investigate whether CH and CL flower production in Portulaca oleracea is genetically differentiated among populations in association with climatic conditions. Methods First, we conducted growth experiments with P. oler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, cleistogamy expression in C. broussonetii would be mainly prompted by abiotic factors such as degraded microenvironmental conditions, as documented elsewhere for other CL species ( e.g . Uphof 1938; Stojanova et al 2020; Furukawa et al 2020; Sternberger et al 2020). However, despite the lack of influence of the pollination environment in the expression of cleistogamy in our study sites, we did observe differences in the relative reproductive success between CH and CL flowers in burned sites, where CH flowers set more seeds than CL flowers in both low and high fire frequency conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cleistogamy expression in C. broussonetii would be mainly prompted by abiotic factors such as degraded microenvironmental conditions, as documented elsewhere for other CL species ( e.g . Uphof 1938; Stojanova et al 2020; Furukawa et al 2020; Sternberger et al 2020). However, despite the lack of influence of the pollination environment in the expression of cleistogamy in our study sites, we did observe differences in the relative reproductive success between CH and CL flowers in burned sites, where CH flowers set more seeds than CL flowers in both low and high fire frequency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as soil moisture and nutrition, light levels and plant size may influence the production of CL and CH flowers (Lu 2002; Munguía‐Rosas et al 2013; Furukawa et al 2020). At the microsite scale, abiotic resource limitation usually increases cleistogamy expression, as this phenotype provides a high ratio of fitness/cost returns, maximizing reproductive success (Lloyd 1984; Veena & Nampy 2019; Stojanova et al 2020; Sternberger et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cleistogamy has evolved independently multiple times (Desfeux et al, 1996), and there are few, if any, documented cases of loss of the CH flowers. This peculiar reproductive strategy, and why it is maintained, has puzzled biologists for a long time, and continues to do so because it goes against the prediction that mixed mating is not evolutionarily stable (Goodwillie et al, 2005; Oakley and Winn, 2008; Winn and Moriuchi, 2009; Ansaldi et al, 2019; Furukawa et al, 2020). Yet, experimental studies have revealed certain conditions (e.g., pollen limitation) that would allow mixed mating systems to be evolutionarily stable (Albert et al, 2011; Stojanova et al, 2020).…”
mentioning
confidence: 99%
“…The strategy for producing the two flower morphs may be selected under certain circumstances. Factors such as light quantity, soil moisture, temperature, herbivory, and plant size can affect the relative number of CH and CL flowers produced (Waller, 1980; Berg and Redbo‐Torstensson, 1999; Forrest and Thomson, 2008; Furukawa et al, 2020; Sternberger et al, 2020). According to the ‘adaptive plasticity hypothesis,’ cleistogamy is favored under heterogeneous and stressful environments (e.g., water deficient and scarce pollinators), which are unsuitable for cross‐pollination (Schoen and Lloyd, 1984; Culley, 2002; Albert et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation